Creating and Governing Cultural Heritage in the European Union The European Heritage Label - Lähdesmäki, Tuuli (Taylor & Francis, 2020)
Creating and Governing Cultural Heritage in the European Union provides an interdisciplinary examination of the ways in which European cultural heritage is created, communicated, and governed via the European Heritage Label scheme. Drawing on ethnographic field research conducted at sites in ten countries that have been awarded with the European Heritage Label, the authors of the book approach heritage as an entangled social, spatial, temporal, discursive, narrative, performative, and embodied process. Recognising that heritage is inherently political and used by diverse actors as a tool for re-imagining communities, identities, and borders, and for generating notions of inclusion and exclusion in Europe, the book also considers the idea of Europe itself as a narrative. Chapters tackle issues such as multilevel governance of heritage; geopolitics of border-crossings and border-making; participation and non-participation; and embodiment and affective experience of heritage. Creating and Governing Cultural Heritage in the European Union advances heritage studies with an interdisciplinary approach that utilises and combines theories and conceptualizations from critical geopolitics, political studies, EU and European studies, cultural policy research, and cultural studies. As such, the volume will be of interest to scholars and students engaged in the study of heritage, politics, belonging, the EU, ideas and narratives of Europe.